2016
DOI: 10.1111/bjd.14245
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, phase IIa exploratory trial to assess the safety and preliminary efficacy of LEO 43204 in patients with actinic keratosis

Abstract: SummaryBackground LEO 43204 is a novel ingenol derivative in development for the treatment of actinic keratosis. Objectives To compare the safety and preliminary efficacy of three doses of LEO 43204 with ingenol mebutate in actinic keratoses (AKs). Methods Patients with at least three visible, discrete, nonkeratotic AKs on four separate selected treatment areas on the forearms received LEO 43204 gel (0Á025%, 0Á05% and 0Á075%) and ingenol mebutate 0Á05% gel, by investigator-blinded, randomized allocation, for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Phase IIa data have indicated that ingenol disoxate (0Á025%, 0Á05% and 0Á075%) has comparable safety and efficacy with ingenol mebutate when applied on the forearms for two consecutive days (maximum treatment area 25 cm 2 ). 10 However, in clinical practice, the majority of patients may require treatment for skin areas > 25 cm 2 . In the pivotal ingenol mebutate trials, one dose regimen was used to treat both the face and the scalp, but lower efficacy has been observed when treating AK on the scalp compared with the face, 8,11 warranting a tailored regimen for the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase IIa data have indicated that ingenol disoxate (0Á025%, 0Á05% and 0Á075%) has comparable safety and efficacy with ingenol mebutate when applied on the forearms for two consecutive days (maximum treatment area 25 cm 2 ). 10 However, in clinical practice, the majority of patients may require treatment for skin areas > 25 cm 2 . In the pivotal ingenol mebutate trials, one dose regimen was used to treat both the face and the scalp, but lower efficacy has been observed when treating AK on the scalp compared with the face, 8,11 warranting a tailored regimen for the former.…”
Section: Discussionmentioning
confidence: 99%
“…Ingenol disoxate is a novel ingenol derivative in development for the field treatment of AK that has been selected for improved thermostability, direct cellular cytotoxicity and the ability to induce proinflammatory mediators (data on file). Phase IIa data have indicated that ingenol disoxate (0·025%, 0·05% and 0·075%) has comparable safety and efficacy with ingenol mebutate when applied on the forearms for two consecutive days (maximum treatment area 25 cm 2 ) . However, in clinical practice, the majority of patients may require treatment for skin areas > 25 cm 2 .…”
mentioning
confidence: 99%
“…Although data indicated relatively higher ingenol disoxate skin exposure levels, the magnitude and temporal pattern of the local skin response (LSR) mirrored the effect of ingenol mebutate in the hairless guinea pig; an extensively used model to assess LSRs [37]. Translation to the clinical setting has subsequently been confirmed by the demonstration of a similar LSR profile of ingenol mebutate and ingenol disoxate at similar dose strengths in patients with AK [38]. …”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of ingenol disoxate we have identified a molecule that fulfills our drug candidate profile criteria in terms of both chemical stability and preclinical efficacy. Ingenol disoxate is currently in Phase 3 clinical development and was recently shown to be an efficacious and well-tolerated topical field treatment for AK, further underscoring the therapeutic potential of this novel ingenol derivative in non-melanoma skin cancers [38]. …”
Section: Discussionmentioning
confidence: 99%
“…In their randomized controlled phase IIa trial, Sinnya and colleagues present promising data on the efficacy and safety of a new derivate of ingenol mebutate in the treatment of AK, LEO 43204 . Patients applied different concentrations of LEO 43204 and ingenol mebutate to randomly assigned fields for 2 days.…”
mentioning
confidence: 99%